PENGGUNAAN STRATEGI REPRESENTASI VISUAL DALAM PEMBELAJARAN APRESIASI PROSA FIKSI - Pratiwi, Yuni (Diksi, 2006)
The use of a representational strategy in the teaching of prose fictionappreciation could give students more chances to use non-linguistic symbols inexpressing the results of their literature appreciation. The use of non-linguisticsymbols has the power of driving away the boredom students experience in usingthe usual appreciation techniques as well as giving them more chances to createand build their personal meaning in social interaction, enhancing their criticalthinking, and empowering them in giving strong argumentation in enjoyablelearning contexts. The non-linguistic symbols are many in kind. They are, amongothers, colored pie charts, sketches, measuring scale figures, and comic pictures.Keywords: visual